Re-thinking visitor loyalty at ‘once in a lifetime’ nature-based tourism destinations: Empirical evidence from Purnululu National Park, Australia - Pinkus, E.; Moore, S.; Taplin, Ross; Pearce, J. (Elsevier BV, 2016)
Visitor loyalty with respect to national parks has been under-researched, especially for iconic or ‘once in a lifetime’ tourism destinations. This study reports on results from a survey of 529 visitors to the remote and iconic Purnululu National Park, Australia. An investigation of the relationships between loyalty, satisfaction and service quality indicates loyalty has multiple dimensions, including word of mouth recommendations and intention to revisit, with each having a different relationship with satisfaction and service quality. These findings, plus the weak correlation between revisiting and positive word of mouth intentions, suggests a need to reconceptualise loyalty in relation to ‘once in a lifetime’ destinations. For these tourism destinations, there may be other ways for visitors to demonstrate loyalty and the associated means for measuring it, rather than intention to revisit. Loyalty may be a transferred concept, with loyalty to one iconic destination resulting in visitation to other, similar destinations. Management implications Traditional measures of visitor loyalty may not be applicable to iconic or ‘once in a lifetime’ tourism destinations. Managers of these types of tourism destinations may be best served measuring word of mouth recommendations or intentions of visitors to engage in positive communications about the destination as a means of determining visitor loyalty. Although potentially difficult to influence, a focus on visitor satisfaction rather than service quality would be beneficial.